On the Fekete-Szego problem for alpha-quasi-convex functions - Abdel-Gawad, H. R. (Tamkang Journal of Mathematics, 2000)
Let $ Q_\alpha(\alpha\ge 0)$ denote the class of normalized analytic alpha-quasi-convex functions $ f$, defined in the unit disc, $ D=\{z:|z|<1\}$, by the condition $$ \hbox{Re}\left[(1-\alpha){f'(z)\over g'(z)}+ \alpha {(zf'(z))'\over g'(z)}\right]>0,$$ Where $ f(z)=z+\sum_{n=2}^\infty a_n z^n$ and where $ g(z)=z+\sum_{n=2}^\infty b_nz^n$ is a convex univalent function in $ D$. Sharp upper bounds are obtained for $ |a_3-\mu a_2^2|$, when $ \mu\ge 0$.